2008
DOI: 10.4049/jimmunol.180.9.6070
|View full text |Cite
|
Sign up to set email alerts
|

Loss of STAT3 in CD4+ T Cells Prevents Development of Experimental Autoimmune Diseases

Abstract: Th17 cells are implicated in CNS autoimmune diseases. We show that mice with targeted-deletion of Stat3 in CD4+ T cells (CD4Stat3−/−) do not develop experimental autoimmune uveoretinitis (EAU) or experimental autoimmune encephalomyelitis. Defective Th17 differentiation noted in CD4Stat3−/− mice is compensated by exaggerated increases in Foxp3-, IL-10-, IL-4-, and IFN-γ-expressing T cells, suggesting critical roles of STAT3 in shaping Ag-specific CD4+ T cell repertoire. In mice with EAU, a high percentage of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
226
4
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 256 publications
(247 citation statements)
references
References 25 publications
15
226
4
2
Order By: Relevance
“…By day 21-28, there was a substantial reduction in inflammatory cells in the retina with diminution of clinical symptoms of disease occurring thereafter. Consistent with the requirement of STAT3 for Th17 development, STAT3KO mice did not develop EAU [19] and pathologic lesions in WT mice retina correlated temporally with increase in Th17 in LNs (Fig. 2B).…”
Section: Th17-dp Cells Persist In Peripheral Tissues After Recovery Fsupporting
confidence: 75%
See 2 more Smart Citations
“…By day 21-28, there was a substantial reduction in inflammatory cells in the retina with diminution of clinical symptoms of disease occurring thereafter. Consistent with the requirement of STAT3 for Th17 development, STAT3KO mice did not develop EAU [19] and pathologic lesions in WT mice retina correlated temporally with increase in Th17 in LNs (Fig. 2B).…”
Section: Th17-dp Cells Persist In Peripheral Tissues After Recovery Fsupporting
confidence: 75%
“…Specifically, we investigated whether Th17-DP is present in blood, LNs or retina of mice with EAU, a model of uveitis [14]. STAT3KO mice and WT mice were immunized with interphotoreceptor-retinoid-binding-protein (IRBP) in CFA and EAU was assessed by histology [19]. In line with the previous reports, initial signs of EAU appeared 7-12 d after immunization, with full-blown disease developing by day 14-16 post-immunization ( Fig.…”
Section: Th17-dp Cells Persist In Peripheral Tissues After Recovery Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, T cells other than CD4 1 Th cells secrete IL-17 and function in autoimmunity and protective immunity to pathogens and the term 'Th17' should only be used when it is shown that IL-17 is produced by CD4 1 T cells. Furthermore, while Th17 can be clearly identified as a distinct population of CD4 1 T cells from Th1 cells and to employ distinct transcriptional factors for their development, a population of cells that coexpress IL-17 and IFN-g have been identified [32][33][34]. IL-17 1 IFN-g 1 CD4 1 and IL-17 1 IFN-g À CD4 1 T cells express receptors for both IL-12 and IL-23, and stimulation with IL-12 enhances IFN-g production and T-bet expression [35].…”
Section: T-cell Subtypes That Secrete Il-17mentioning
confidence: 99%
“…STAT-3 has been shown to regulate IL-6 and IL-23 induced expression of RORgt and IL-17 production by CD4 1 T cells [66,67]. Furthermore STAT3-defective mice have reduced IL-17 production and are resistant to the development of experimental autoimmune uveoretinitis [33]. It has also been suggested that the NFAT and MAP kinase pathways are involved TCR-induced IL-17 production by human T cells [68].…”
Section: Intracellular Signalling Molecules and Transcription Factorsmentioning
confidence: 99%